2008
DOI: 10.1515/cclm.2008.297
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide testing in primary care patients

Abstract: The evaluation of cardiac endocrine function by means of automated robust assays has permitted the introduction of a cheap and powerful clinical tool. Plasma concentration of B-type-related natriuretic peptides is a marker of either hemodynamic or neurohormonal stress on the heart and has been validated within the diagnostic and prognostic domain in patients with suspected or ascertained heart failure, mostly in the in-hospital setting. Evidence is growing, supporting an out-of-hospital use, namely in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…5). These findings represent the rationale for evaluating the diagnostic accuracy of BNP and NT-proBNP levels in screening programs including general population or primary care patients [51,52]. Moreover, some recent studies reported that patient with heart failure have also greatly increased circulating proBNP levels compared to healthy subjects [22,[26][27][28].…”
Section: Pathophysiological Clinical and Pharmacological Considerationsmentioning
confidence: 99%
“…5). These findings represent the rationale for evaluating the diagnostic accuracy of BNP and NT-proBNP levels in screening programs including general population or primary care patients [51,52]. Moreover, some recent studies reported that patient with heart failure have also greatly increased circulating proBNP levels compared to healthy subjects [22,[26][27][28].…”
Section: Pathophysiological Clinical and Pharmacological Considerationsmentioning
confidence: 99%
“…The widespread diffusion of automated assays of BNP and NT-proBNP has furnished a novel tool for diagnosis, prognostic evaluation, and guide to treatment of overt HF, as well for the screening of asymptomatic left ventricular dysfunction in the general population (2,7), with a potential use in primary care (8). Recent evidence has challenged, however, the specificity of all commercial assays for BNP and NT-proBNP, indicating a significant cross-reactivity with the precursor proBNP 1-108 , variable for each assay (9).…”
mentioning
confidence: 99%
“…tomatic subjects at intermediate to high risk for HF, or for differential diagnosis in patients with dyspnea. Evidence is growing, supporting an out-of-hospital use of natriuretic peptide assays: their implementation in screening programs and diagnostic algorithms in primary care might contribute to decrease the apparent disparity between the general practitioner and the specialist approach to disease management (8).…”
mentioning
confidence: 99%